Varieties of American Sufism: Islam, Sufi orders, and authority in a time of transition - Bazzano, Elliott; Hermansen, Marcia K. (SUNY Press, 2020)
Acknowledgments -- Introduction / Marcia Hermansen -- The Message in Our Time: Changing Faces and Identities of the Inayati Order in America / Geneviève Mercier-Dalphond -- The Golden Sufi Center: A Non-Islamic Branch of the Naqshbandiyya-Mujaddidiyya / William Rory Dickson -- The Bawa Muhaiyaddeen Fellowship: Diverse Identities and Negotiated Spaces / Merin Shobhana Xavier -- A Shadhiliyya Sufi Order in America: Traditional Islam Meets American Hippies / Elliott Bazzano -- The Mevlevi Order of America / Simon Sorgenfrei -- From the Balkans to America: The Alami Tariqa in Upstate New York / Julianne Hazen -- 'There is an 'I' deeper than me': The Ansari Qadiri Rifa'i Tariqa and Transcendence in America / Melinda Krokus -- When the Divine Flood Reached New York: The Tijani Sufi Order among Black American Muslims in New York City / Rasul Miller -- Contributors -- Index.